Perceptions Of Madrassa Students And Teachers Towards English Language Learning - Syed Sajjad Ali (University of Chitral Journal of Linguistics and Literature, 2020)
The purpose of this descriptive research study is to find out the perceptions of students andteachers about the problems and challenges in learning and teaching of English language inMadrassas located in urban area of District Mardan. The main objectives of the study are toassess the attitude of both the students and teachers towards English language; to find out therequired facilities for the teaching and learning of English and to put forward therecommendations of the students and teachers for the eradication of the problems and challengesto English language learning and teaching in Madrassas. The population of the research studyconsist of all Madrassas and all male students and teachers in Urban Madrassas in DistrictMardan. The researchers use convenient sample for the selection of Madrassas. Selection ofstudents is based on thirty percent proportionate sample; while teachers are selected on the basisof hundred percent proportionate samples accordingly. Two separate questionnaires are theinstrument for data collection. The questionnaires comprised on both closed and open endeditems. The collected data were analyzed using percentage and thematic analysis. Findings of thestudy revealed that there are no proper facilities for the teaching of English language. The resultsof this research study may be helpful for the policy makers to emphasize more on the importanceof English language learning in Madrassas across Pakistan and Khyber Pakhtunkhwa inparticular.